Microbiological profile and antimicrobial susceptibility in children with perforated appendicitis at Dr. Sardjito General Hospital, Yogyakarta - . Rochadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Acute appendicitis is the most common surgical cause of acute abdominal pain in children.Perforated appendicitis is the major complication of acute appendicitis with incidencein children of 30-40%. Perforated appendicitis should be operated immediately alongwith the administration of broad-spectrum antibiotics. The aim of this study isto analyzethe microbiological profile and determine the antimicrobial susceptibility in childrenwith perforated appendicitis at Dr. Sardjito General Hospital, Yogyakarta, Indonesia.Weanalyzed the pus from the perforated appendicitis patients who underwent surgery at Dr.SardjitoGeneral Hospital from January 2005 to September 2009. Escherichia coli (43%)was the most common aerobic bacteria found in children with perforated appendicitis,followed by Pseudomonas aeruginosa (26%), Klebsiellapneumonia (11%), Streptococcus(11%), and Proteus mirabilis (3%).The most sensitive antibiotics were imipenem,phosphomycin, amikacin and netilmicin, followed by the 4th and the 3rd generation ofcephalosporin, amoxicillin, ampicillin, and trimethoprim/sulfamethoxazole. In addition,there was no statistically significant difference in terms of resistant and sensitivity betweenthe 4th generation cephalosporin compared to phosphomycin, netilmicin, or imipenem(p > 0.05). In conclusion, the most common bacteria found in perforated appendicitisin Dr. Sardjito General Hospital is E.coli. The administration of the 4th generation ofcephalosporin might be appropriate for the children with perforated appendicitis.